Early results of micro-deformation measurements in Magdalena Jama (Slovenia) by a vertical static pendulum - Kalenda, Pavel; Neumann, Libor; Šebela, Stanka (Acta Carsologica, 2013)
Vertical static pendulums have been installed in mines or caves in Central Europe since 2007. Two-dimensional optical measurement of the tilt of a rock mass and continuous fully digital on-line evaluation of results makes possible the detection of a small tilt of the surroundings with a resolution of tens of nanoradians or the deformation of the surroundings in the horizontal plane with resolution of hundreds of nanometres. The paper describes the measurement device and the first results of the measurements in Magdalena Jama, which is part of the Postojna Cave System (Slovenia). The correlation of deformation between distant stations shows the existence of stress variations that are not only of local origin (high floods, local seismicity, and aseismic deformations). The stress field has a wider, and not only regional, character with effects that can be observed very far from the origin.